Determination of the ionic conductivity of Sr-doped lanthanum manganite by modified Hebb–Wagner technique. (April 2016) - Miruszewski, T.; Karczewski, J.; Bochentyn, B.; Jasinski, P.; Gazda, M.; Kusz, B.
Abstract: The Hebb–Wagner polarization method with the electron blocking electrode has been discussed in this paper in aim to determine a partial ionic conductivity of Sr-doped lanthanum manganite. The "limiting current" in the proposed system was measured using the two-point DC technique with additional Pt electrode between LSM and blocking electrode. The electrochemical model based on bulk diffusion processes and Boltzmann statistics has been also described. The ionic conductivity calculated with the use of proposed model for La0.7 Sr0.3 MnO3+ δ was 5.3×10 −4  S cm −1 at 800 °C and the activation energy of ionic conductivity was found to be (0.60±0.02) eV. This result is in agreement with previous literature reports and indicates the workability of the modified Hebb–Wagner system. Highlights: Modified Hebb–Wagner polarization method was tested. Computational model to determine the ionic conductivity of LSM was used. New interpretation of obtained I–U curve was proposed. Estimation of the activation energy for ionic conductivity was performed. The ionic conductivity of La0.7 Sr0.3 MnO3 reaches 5.3 × 10 −4  S cm −1 at 800 °C.